Review of electromyography control systems based on pattern recognition for prosthesis control application - Ahmad, Siti Anom; Ishak, Asnor Juraiza; Md Ali, Sawal Hamid; Chappell, Paul H. (American-Eurasian Network for Scientific Information, 2011)
Electromyographic control is a technique that involve with the detection, processing and classification of the electromyography signal that could be applied in human-assisting robots, prosthesis application or rehabilitation devices. This paper reviews recent research and development electromyographic control systems with an emphasis on pattern recognition control for prosthesis application. Various methods used in the different stages of the pattern recognition based control system are discussed in details.